Comparing Performance within a Virtual Supermarket of Children with Traumatic Brain Injury to Typically Developing Children: A Pilot Study. (October 2013) - Erez, Neta; Weiss, Patrice L.; Kizony, Rachel; Rand, Debbie
The purpose of this study was to determine the usability of a virtual reality environment for pediatric traumatic brain injury (TBI) by assessing the performance of a simple virtual shopping task and comparing their results to typically developing peers. Twenty children with TBI and 20 typically developing children, matched in age and sex, "shopped" for four items in a virtual supermarket (VMall). A short feedback questionnaire, Borg's scale of perceived exertion, and the Zoo Map subtest from the Behavioral Assessment of the Dysexecutive Syndrome for Children were also administered. All of the children were able to complete a four-item test within the VMall. Overall, good usability was obtained. A significant difference in shopping performance was found between the two groups; the mean shopping time and number of mistakes was higher for the children with TBI. The use of a short shopping test within a functional virtual environment enabled detection of poorer performance of children with TBI that may be due to executive function deficits. Because the task was enjoyable and motivating, the VMall may also be used to enhance participation in instrumental activities of daily living and play for children with TBI.